Markets for data. (13th March 2020) - Koutroumpis, Pantelis; Leiponen, Aija; Thomas, Llewellyn D W
Abstract: Although datasets are abundant and assumed to be immensely valuable, they are not being shared or traded openly and transparently on a large scale. We investigate the nature of data trading with a conceptual market design approach and demonstrate the importance of provenance to overcome appropriability and quality concerns. We consider the requirements for efficient data exchange, comparing existing trading arrangements against efficient market models and show that it is possible to achieve either large markets with little control or small markets with greater control. We describe some future research directions.